Pengaruh Motivasi Belajar dan Kecemasan Matematika Terhadap Hasil Belajar Matematika Siswa Melalui Kemampuan Metakognisi - Sartika Arifin; Nurfadilah Mahmud; Sulfianti (Mandalika Mathematics and Educations Journal, 2022)
The purpose of this study was to determine the effect of learning motivation and mathematics anxiety on mathematics learning outcomes through metacognition ability. This research is an ex-post facto research with a sample of 78 students, namely class XI MIPA 1 and class XI MIPA 3 SMA who were selected using cluster random sampling. The data collection technique used the following instruments: learning motivation questionnaire, mathematics anxiety questionnaire, metacognition ability questionnaire, and mathematics learning outcomes. The data were analyzed using descriptive statistics and inferential statistics with the trimming model path analysis. The results showed that: (1) student learning motivation has a direct and significant effect on students' metacognition abilities, (2) learning motivation has an indirect effect on students' mathematics learning outcomes through students' metacognition abilities, (3) student learning anxiety has an indirect effect on student learning outcomes through k students' metacognition abilities